Islamic Spirituality and Modern Challenges - Omer, Spahic (Dar Al Wahi Publication, 2021)
Islam and Muslims stand today at the crossroads. They are being battered by the ferocious storms of globalization and westernization, which are buoyed by the ideological potencies of modernism, postmodernism and liberalism. For Muslims, the end of physical colonialism spelled a series of false dawns, as other more subtle forms of imperialism took over. They proved almost as successful and devastating for the affected peoples and their countries as the former. It would be fair to say that Muslims never fully recovered from the impacts of the physical subjugation. At the same time, in addition, they had to deal with the ideological assaults from all sides, as well as with the downright cultural invasions. That greatly exacerbated the situation, stretching the resistance and defence capacities - both at the individual and institutional levels - to breaking point. The 21st century with a great many global changes and challenges is well under way. However, most Muslims recurrently exhibit that they have learned nothing, or very little, from myriads of painful episodes in history, that they have little in store to overcome and pass the current trials, and that they are ill-prepared for the future. This means that if at first, Muslims were largely victimized by others, later however, they became the sole makers of their own cultural and civilizational unfortunate destiny. This book is an anthology of twenty nine essays, one assay accounting for one chapter. The book deals with various aspects of the relationship between Islam and its spirituality and culture, on the one hand, and the ideological as well as cultural challenges of modern times, on the other. It aims to be an eye-opener and to inspire a critical and creative thinking. The themes covered revolve around the following thrusts: the meaning and significance of Islamic spirituality; the Islam-versus-modern-times dialectics; revisiting the concepts of life, civilization, worship, beauty, happiness, knowledge and justice; the relationship between the truth and falsehood, knowledge and ignorance, and between light and darkness; the implications of living the Islamic monotheistic message for the earthly missions of individuals and societies; and a number of lessons in connection with the COVID-19 pandemic.